Challenges and Benefits of Implementing AI in Timber Construction for Circular Economy Goals - Mohsen Ghobadi; Samad M. E. Sepasgozar (Buildings)
Artificial intelligence (AI) is considered an essential enabler of a circular economy (CE) in the construction industry. AI can significantly enhance the efficiency of applying innovative CE practices in other construction projects. However, it has not yet been fully integrated into the application of CE principles and has explicitly been overlooked in the context of timber construction. This study aims to bridge this gap by examining the potential contributions of AI applications to achieving CE in timber construction, as well as identifying the associated benefits and challenges. Through a mixed-methods approach, the research utilizes both qualitative data, collected through timber construction industry interviews, and quantitative analysis to explore professional construction perspectives and uncover actionable insights. The findings highlight the transformative potential of AI to enhance sustainability and operational efficiency in timber construction. Moreover, six potential benefits and 11 challenges for integrating AI and a CE in timber construction are identified that can act as an accelerator for advancing circularity in timber construction. Based on the results, the reduction in construction waste and facilitating the deconstruction and reuse process emerge as the most important benefits. Data obstacles, technological integration, finance and resources, and organizational and industry are determined as the main challenges. This study makes novel contributions to the field by providing empirical evidence in the form of qualitative and quantitative data, in addition to practical recommendations for advancing the integration of AI to promote CE goals and improve sustainability in the timber construction sector.